1998
DOI: 10.1038/bjc.1998.540
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that an HLA-DQA1-DQB1 haplotype influences susceptibility in childhood common acute lymphoblastic leukaemia in boys provides further support for an infection-related aetiology

Abstract: Summary Comparison of DOA 1 and DOB1 alleles in 60 children with common acute tymphoblastic leukaemia (c-ALL) and 78 newborn infant control subjects revealed that male but not female patients had a higher frequency of DA1*0A101/'O104 and DOB1*0501 than appropriate control subjects. The results suggest a male-associated susceptibility haplotype in c-ALL and supports an infectious aetiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
26
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 15 publications
(1 reference statement)
4
26
0
Order By: Relevance
“…Another important finding in the present study was the male specificity of the HSP association. The sex effect in extended HLA complex associations with childhood ALL has already been reported by us and others (Taylor et al 1998;Dorak et al 1999a, b;Ng et al 2006). Notably, the positive correlation between high HSP serum levels and lung cancer susceptibility is also observed in males only (Suzuki et al 2006).…”
Section: Discussionsupporting
confidence: 64%
“…Another important finding in the present study was the male specificity of the HSP association. The sex effect in extended HLA complex associations with childhood ALL has already been reported by us and others (Taylor et al 1998;Dorak et al 1999a, b;Ng et al 2006). Notably, the positive correlation between high HSP serum levels and lung cancer susceptibility is also observed in males only (Suzuki et al 2006).…”
Section: Discussionsupporting
confidence: 64%
“…A study of HLA haplotypes in common-ALL has shown that a specific DQA1/DQB1 haplotype is associated with susceptibility in males, but not in females. 16 Together these results and the current data on incidence trends support the hypothesis that common-ALL is aetiologically linked to delayed exposure to common infections. 17 In contrast to ALL, AML has displayed stable incidence rates over the 45-year period and, from previous studies based on the MCTR, 14,15 has shown neither seasonal variation nor space-time clustering.…”
Section: Discussionsupporting
confidence: 61%
“…However, very few studies have focused on possible familial links between autoimmunity and hematopoietic malignancies in adults. Familial Hodgkin's lymphoma, and possibly also acute lymphocytic leukemia, is linked to HLA class II (41,42), as is the case for most autoimmune diseases (43). Studies in both humans and mice have demonstrated associations between autoimmune disorders in the family and risk of CLL (20,44).…”
Section: Ekströ M Et Almentioning
confidence: 99%